2023
DOI: 10.1002/jmri.29056
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Interstitial Fluid With MRI: A Narrative Review on the Associations of Altered Interstitial Fluid With Vascular and Neurodegenerative Abnormalities

Gerhard S. Drenthen,
Elles P. Elschot,
Noa van der Knaap
et al.

Abstract: Interstitial fluid (ISF) refers to the fluid between the parenchymal cells and along the perivascular spaces (PVS). ISF plays a crucial role in delivering nutrients and clearing waste products from the brain. This narrative review focuses on the use of MRI techniques to measure various ISF characteristics in humans. The complementary value of contrast‐enhanced and noncontrast‐enhanced techniques is highlighted. While contrast‐enhanced MRI methods allow measurement of ISF transport and flow, they lack quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…The DTI-ALPS technique has been widely employed in studies involving aging and small vessel disease cohorts. In all instances, a consistent finding emerged, indicating an inverse correlation between the load of WMH and the diffusion of venous interstitial fluid in the PVS [48]. Research using the DTI-ALPS approach additionally demonstrated diminished fluid dynamics in the venous PVS following occurrences of ischemic stroke [72] and intracerebral hemorrhage [73].…”
Section: Pathologicalmentioning
confidence: 74%
See 1 more Smart Citation
“…The DTI-ALPS technique has been widely employed in studies involving aging and small vessel disease cohorts. In all instances, a consistent finding emerged, indicating an inverse correlation between the load of WMH and the diffusion of venous interstitial fluid in the PVS [48]. Research using the DTI-ALPS approach additionally demonstrated diminished fluid dynamics in the venous PVS following occurrences of ischemic stroke [72] and intracerebral hemorrhage [73].…”
Section: Pathologicalmentioning
confidence: 74%
“…To address non-specificity in DTI interpretations, a multi-compartment modeling approach is employed. This involves acquiring diffusion-weighted images at various b-values or gradient strengths to probe different tissue compartments characterized by distinct diffusion profiles [48]. Examining the diffusion of interstitial fluid within the PVS provides valuable insights into the PVS microstructure, including pathological enlargement and function, such as disruptions in glymphatic flow due to debris presence.…”
Section: Imagingmentioning
confidence: 99%